PEMANFAATAN SENYAWA METABOLIT SEKUNDER KAWISTA (Limonia acidissima) UNTUK PENGELOLAAN DIABETES: TINJAUAN ANALISIS JEJARING FARMAKOLOGI - Hentu, Dina Siti Rahma M.; Muchlisin, M. Artabah; Jamil, Ahmad Shobrun; Astuti, Engrid Juni; Rafikayanti, Agustin (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2024)
This study aims to explore the potential of secondary metabolite compounds from the kawista plant (Limonia acidissima) as antidiabetic agents through an in silico approach. We utilized pharmacological network analysis and analysis of the most important proteins to identify potential protein targets and signaling pathways involved in diabetes regulation. The analysis revealed that secondary metabolite compounds from kawista have the potential to affect various crucial aspects of glucose and lipid metabolism in the body, including through interactions with key proteins such as AKT1. These findings provide new insights into the development of additional therapies for diabetes treatment, and demonstrate the potential of in silico methods in accelerating the discovery and development of new drugs.